Optimalisasi Pembinaan Sepak Bola di Smk Panjatek Untuk Meningkatkan Keterampilan Dasar dan Taktik Bermain - Dini Nurfauziah; Bujang; Ilham Romadhona Lubis; R. Dimas Pandu Satria (PT. Sharia Journal and Education Center, 2024)
Football is one of the most popular sports in the world, including in Indonesia. In the context of education, especially in Vocational High Schools (SMK), football is not only a means to improve physical fitness, but also to shape students' character, such as discipline, teamwork, and leadership. Therefore, football coaching in SMK needs to be optimized to improve basic skills and understanding of playing tactics. This community service program aims to implement a structured approach in football coaching at SMK Panjatek, Bekasi City, with a focus on basic skills (dribbling, passing, shooting) and understanding of game tactics. The results of this program show that students experience significant improvements in technical skills and understanding of game tactics, as well as increased teamwork and competitive spirit.